Perancangan Sistem Rekap Laporan Penjualan Menggunakan Metode Extreme Programming (Studi Kasus Pt. Oscar Mitra Sukses Sejahtera Tangerang) - Rita Amelia; Hardiansyah (CV. Shofanah Media Berkah, 2023)
PT Oscar Living Tangerang Branch is a company that sells furniture offline. due to technological developments and fast data transfer speeds, PT Oscar Living has expanded product sales online. In the midst of this rapid development of information, of course, PT Oscar Mitra Sukses Sejahtera Tbk, Tangerang Branch, has developed its business from what was originally still using reports that were still manual, to something that can be said to be a form of digitization. On the basis of that background, the researcher conducted this research. With the XP Method or Extreme Programming As a system development method this is done to save time in making if there are changes that are deemed necessary or inappropriate. Some of the points that are emphasized more in this research are to make it easier for the admin's work in making reports, reducing damage and loss of data, and also reducing the existence of human error. The expected results of this sales report recap information system are proven to be able to help financial recapitulation easily, are in accordance with user flow, can reduce errors in making sales reports as with the questionnaire that has been wrapped to 15 employee respondents of PT Oscar Mitra Sukses Sejahtera.